Heart disease complicating pregnancy as a leading cause of maternal deaths in LMIC settings: the Sri Lankan experienceResearch in context - Ayesh Hettiarachchi; Kapila Jayaratne; Chithramalee De Silva; Hemantha Senanayake; Niroshan Lokunarangoda; Suneth Agampodi (Elsevier, 2023)
Summary: Background: Heart disease (HD) is one of the leading indirect causes of maternal deaths worldwide, both in high- and low- and middle-income countries (LMICs). This study aims to describe maternal deaths due to cardiovascular disease complicating pregnancy in Sri Lanka. Methods: The national Maternal Death Surveillance Response (MDSR) system in Sri Lanka investigates all female deaths during pregnancy and 12 months after delivery. These maternal death investigation records were perused in this analysis. Maternal deaths from 2006 to 2018 with HD complicating pregnancy as the immediate or underlying cause of death were re-coded using the ICD-11 classification. Findings: Of the 2855 pregnancy-related deaths reported to the MDSR from 2006 to 2018, 1646 (57.7%) were confirmed as maternal deaths. Of those, 284 (17.25%) were attributed to HD complicating pregnancy. The cause-specific maternal mortality ratio due to heart disease from 2006 to 2018 was 7.24 per 100,000 live births. Rheumatic heart disease was the leading cause of HD (60, 21.1%), while cardiomyopathies (59, 20.7%) and congenital anomalies (34, 12.0%) accounted for a sizeable share. Medically contraindicated pregnancies accounted for 54 (19%) deaths. Application of the 3-delay model identified 186 (65.5%) cases with possible delays. Out of all deaths, 158 (55.6%) cases were categorized as preventable. Interpretation: Preventing maternal mortality from HD in LMICs requires a lifecycle approach with situation-specific interventions and highly specialized care. Community awareness, capacity building related to management, and specific infrastructure development will be key strategies. Funding: None.